2016
DOI: 10.1113/jp272453
|View full text |Cite
|
Sign up to set email alerts
|

Passive heat therapy improves endothelial function, arterial stiffness and blood pressure in sedentary humans

Abstract: Key pointsr A recent 30 year prospective study showed that lifelong sauna use reduces cardiovascular-related and all-cause mortality; however, the specific cardiovascular adaptations that cause this chronic protection are currently unknown.r We investigated the effects of 8 weeks of repeated hot water immersion ('heat therapy') on various biomarkers of cardiovascular health in young, sedentary humans.r We showed that, relative to a sham group which participated in thermoneutral water immersion, heat therapy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
269
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(281 citation statements)
references
References 65 publications
9
269
2
1
Order By: Relevance
“…These surprising findings potentially represent novel favourable effects that buttress the vascular benefits previously reported with non-pathophysiological hyperthermia (Umscheif et al 2010;Ohori et al 2012;Laukkanen et al 2015;Brunt et al 2016;Romero et al 2017). To our knowledge, this is the first study to determine the effects of passive heat stress on circulating microparticles.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…These surprising findings potentially represent novel favourable effects that buttress the vascular benefits previously reported with non-pathophysiological hyperthermia (Umscheif et al 2010;Ohori et al 2012;Laukkanen et al 2015;Brunt et al 2016;Romero et al 2017). To our knowledge, this is the first study to determine the effects of passive heat stress on circulating microparticles.…”
Section: Discussionmentioning
confidence: 68%
“…To our knowledge, this is the first study to determine the effects of passive heat stress on circulating microparticles. In addition, Brunt et al (2016) recently reported that 8 weeks of passive whole-body heat therapy (hot water immersion until a rectal temperature of 38.5°C, four or five times per week) reduced resting systolic and diastolic blood pressure, arterial stiffness and carotid intima-media thickness and improved flow-mediated dilatation of the brachial artery in young adults. The notion of therapeutic benefits from controlled hyperthermia is not new (Lee Titsworth et al 2014) but has recently gained interest in large part after a 30 year prospective study (Laukkanen et al 2015) indicating that lifetime sauna use is associated with lower rates of cardiovascular system-related deaths.…”
Section: Discussionmentioning
confidence: 99%
“…12 Heat therapy such as hot water immersion is associated with several health benefits including lower levels of resting blood pressure potentially reducing the risk of cardiovascular diseases CVD. 13 However, in this study, sauna bathing A typical Finnish sauna session is indeed characterized by warming up in the sauna with subsequent cooling and relaxation; this can positively modulate the autonomic system and may further explain the effects on blood pressure reduction. 18,19 Thirdly, heart rate may increase up to 100-150 beats per minute during sauna bathing session 4,20-23 which increases vasodilatation and improves function of the vasculature; these are the same benefits that are associated with low and moderate intensity physical exercise training.…”
Section: Discussionmentioning
confidence: 73%
“…57 Although this relationship does not establish causality, 31,58 it is nonetheless an interesting link that is supported by recent investigations. 59-61 PH appears to improve vascular function, with improvements to flow-mediated dilatation, arterial stiffness and blood pressure reported after 8 weeks of PH. 59 Moreover, Thomas et al have shown that 30 minutes of PH can induce a significant shear stress response and a reduction in mean arterial pressure in patients with peripheral arterial disease.…”
Section: Discussionmentioning
confidence: 97%
“…59-61 PH appears to improve vascular function, with improvements to flow-mediated dilatation, arterial stiffness and blood pressure reported after 8 weeks of PH. 59 Moreover, Thomas et al have shown that 30 minutes of PH can induce a significant shear stress response and a reduction in mean arterial pressure in patients with peripheral arterial disease. 62 Furthermore, in a healthy cohort who underwent matched duration PH or EX, the PH group demonstrated a greater shear stress response compared to that in response to EX.…”
Section: Discussionmentioning
confidence: 97%